Facilitating Salt Marsh Restoration: The Importance of Event-Based Bed Level Dynamics and Seasonal Trends in Bed Level Change - Willemsen, Pim W. J. M.; Horstman, Erik M.; Bouma, Tjeerd J.; Baptist, Martin J.; van Puijenbroek, Marinka E. B.; Borsje, Bas W. (Frontiers in Marine Science, 2022)
Intertidal salt marshes provide a range of valuable ecosystem services which typically increase with marsh width. Understanding the drivers for salt marsh expansion versus retreat is thus key to managers. Previous research highlights the influence of short-term (daily/event) bed level dynamics on germination and establishment and subsequent vegetation presence. However, more recent literature suggests the importance of medium-term seasonal bed level dynamics on viable seed availability and subsequent vegetation presence. This study aims to assess event-based and seasonal bed level dynamics for vegetation presence in natural and semi-natural salt marshes and to provide generic thresholds for vegetation presence. To gain insight into bed level dynamics, data was used from autonomous Optical and Acoustic Surface Elevation Dynamics sensors (O-SED and A-SED) around the edge of natural and semi-natural salt marshes. Sensors were installed at vegetated and unvegetated measurement station Field observations from 22 O-SEDs deployed at 4 well-established natural salt marshes in the Western Scheldt estuary and 4 O-SEDs at a well-established semi-natural salt marsh in the Wadden Sea were reanalyzed. Six novel A-SEDs were deployed at a pioneer semi-natural salt marsh in the Ems-Dollard Estuary. The measurement duration at all salt marshes was at least 1 year. The A-SED sensor was successfully validated against manual measurements. Furthermore, vegetation data and water level data were obtained. No significant difference was observed between natural and semi-natural salt marshes. However, a significant difference between vegetated and unvegetated measurement stations for short-term bed level dynamics was observed. Vegetation was found to be present at locations restricted by short-term bed level variability smaller than or equal to 12 mm, emphasizing the presence of a short-term threshold. Although trends in the non-growing season were significantly different between vegetated and unvegetated stations, seasonal thresholds for vegetation presence were not found. The findings imply that knowledge of bed level-dynamics in well-established natural marshes can be used to predict vegetation presence in constructed semi-natural marshes. The importance of local short-term dynamics for vegetation presence instead of longer-term dynamics highlights possibilities for developing favorable conditions for vegetation presence in marsh restoration projects and the construction of new salt marsh ecosystems.